Análisis jurídico del caso Tagaeri–Taromenane: ¿genocidio o etnocidio? - Pino-Andrade, Edmundo Enrique; Correa-Cepeda, Paola Alejandra; Cordero-Guevara, Carolina Elizabeth (IUSTITIA SOCIALIS, 2021)
Análisis jurídico del caso Tagaeri–Taromenane: ¿genocidio o etnocidio?